High Glucose-Induced Senescent Fibroblasts-Derived Exosomal miR-497 Inhibits Wound Healing by Regulating Endothelial Cellular Autophagy via ATG13 - Changjiang Liu; Yuting Liu; Yifeng Yu; Siyuan Huang; Chao Sun; Dong Zhang; Aixi Yu (Analytical Cellular Pathology)
Conclusions: Our study demonstrated that exosomes from senescent fibroblasts can impair endothelial cell function and impede diabetic wound healing. The underlying mechanism was that fibroblast-derived exosomal miR-497 can target ATG13 to reduce autophagy, offering insight into new therapy for diabetic complications and other diseases.